(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Mariey SA, El-Bialy MA, Khedr RA, Mohamed EN, Meleha AMI, Khatab IA. 2023. Comprehensive evaluation and economic analysis in some barley genotypes under soil salinity. Asian J Agric 7: 20-33. Soil salinity is one of the abiotic stresses that cause a significant reduction in barley production. Understanding the phenotypic and genetic diversity among Barley genotypes is necessary to improve barley salt tolerance. Herne comprehensive sets of morph-physiological, grain quality traits and Simple Sequence Repeat (SSR) markers combined with economic analysis were done to determine the phenotypic and genetic variation of eight barley genotypes under salinity stress during seasons 2019/2020 and 2020/2021. High genetic variation was observed among studied genotypes for all measured traits. Salinization caused a significant increase in (Sodium content, soluble carbohydrate content, and crude protein content %) in sensitive genotypes (Giza 132 and line 1). SSRs markers generated clear patterns with high polymorphism with 31 alleles by an average of 2.07 alleles per locus. Out of 15 SSR markers, nine (Bmac 0209, Bmag 0011, Bmag 125, Bmac 0871, Bmag 770, Bmac 701, Bmag 0387, Bmac316, and Bmag 0009) were highly useful in distinguishing tolerant and sensitive Barley genotypes. Soil salinity decreased the benefit-cost ratio for Giza 123,136 and 137, which appear beneficial as salt-tolerant cultivars. Those cultivars had low reductions for almost studied traits and had the highest grain yield production due to increasing the farmer’s income under salt affect area.